A Stepwise-Clustered Simulation Approach for Projecting Future Heat Wave Over Guangdong Province - Ren, Jiayan; Huang, Guohe; Li, Yongping; Zhou, Xiong; Xu, Jinliang; Yang, Zhifeng; Tian, Chuyin; Wang, Feng (Frontiers in Ecology and Evolution, 2021)
Heatwave is an important meteorological extreme event related to global warming, but little is known about the characteristics of future heatwave in Guangdong. Therefore, a stepwise-clustered simulation approach driven by multiple global climate models (i.e., GCMs) is developed for projecting future heatwave over Guangdong under two representative concentration pathways (RCPs). The temporal-spatial variations of four indicators (i.e., intensity, total intensity, frequency, and the longest duration) of projected heatwave as well as the potential changes in daily maximum temperature (i.e., Tmax) for future (i.e., 2006 – 2095) and historical (i.e., 1976 – 2005) periods were analyzed over Guangdong. The results indicated that Guangdong would endure notable increasing annual trend in the projected Tmax (i.e., 0.016 – 0.03 °C per year under RCP4.5 and 0.027 – 0.057 °C per year under RCP8.5). Evaluations of the multiple GCMs and their ensemble suggested that the developed approach performed well, and the model ensemble was superior to any single GCM in capturing the features of heatwave. The spatial patterns and interannual trends displayed that Guangdong would undergo serious heatwaves in the future. The variations of intensity, total intensity, frequency, and the longest duration of heatwave are likely to exceed 5.4 °C per event, 24 °C, 25 days, and 4 days in the 2080s under RCP8.5, respectively. Higher variation of those would concentrate in eastern and southwestern Guangdong. It also presented that severe heatwave with stronger intensity, higher frequency, and longer duration would have significant increasing tendencies over all Guangdong, which are expected to increase at a rate of 0.14%, 0.83%, and 0.21% per year under RCP8.5, respectively. Over 60% of Guangdong would suffer the moderate variation of heatwaves to the end of this century under RCP8.5. The findings can provide decision makers with useful information to help mitigate the potential impacts of heatwaves on pivotal regions as well as ecosystems that are sensitive to extreme temperatures.